PROBLEMS OF DRUG THERAPY IN PATIENTS WITH TYFOID FEVER AT THE INSTALLATION OF AT-TAQWA ISLAM HOSPITAL GUMAWANG BELITANG PERIOD JANUARY - DECEMBER 2021 - Yunita Yunita; Amelia Soyata (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
Salmonella typhi is a bacterium that causes typhoid fever infection which attacks the digestive tract. Indonesia is an endemic disease, the incidence of typhoid fever cases is 358 to 810 cases per 100,000 population with a percentage of 64%. to find out the treatment of typhoid fever patients who are indicated not to pay attention to the PCNE V9.00 code, namely: there are symptoms that are not treated, to find out whether there are incidents that may be detrimental in the application of drug therapy, treatment that is not needed in treating typhoid fever patients at RSI At-Taqwa Gumawang Belitang. This study used a descriptive method, and data collection was carried out using a retrospective system from the medical records of typhoid fever patients who were hospitalized at the At-Taqwa Islamic Hospital Gumawang Belitang for the period January-December 2021. From medical record data that met the inclusion criteria, namely 80 patients ( 80%), found 14 cases (17.5%) who had problems with drug therapy, these cases were dominant in male patients, namely 43 patients (53.75%) than female patients, namely 37 patients (46.25%). the majority of these patients were aged less than 1 year to 50 years with a total of 68 patients (78.75%), the highest frequency of use of antibiotics was a single antibiotic in 73 patients (91.25%) while combination antibiotics were 7 patients (8.75%) ), the average length of stay was <3 days for 43 patients (53.75%), while > 3 days for 37 patients (46.25%), drug therapy problems according to PCNE V9.00 code, namely P2.1 with 7 cases (8.75%), P1.3 in 4 cases (5.00%), P3.2 in 3 cases (3.75%).